A case of successfully treated fetal supraventricular tachycardia in the late first trimester - Wiecheć, Marcin; Nocuń, Agnieszka; Chęciński, Paweł; Basista-Broda, Jagoda (Prenatal Cardiology, 2023)
We present a case of early diagnosed fetal supraventricular tachycardia in the 13th week of gestation. Fetal supraventricular tachycardia was confirmed at the reference centre with a ventriculo-atrial to atrio-ventricular (VA/AV) interval ratio of 1.06, indicating a form of tachycardia with a borderline VA interval. The ventricular inflows were characterized by monophasic filling without any signs of atrio-ventricular insufficiency. The ductus venosus demonstrated an abnormal velocimetry. Given the severity of the condition of the fetus, the medical team faced the challenge of quickly implementing transplacental therapy and the need to rule out trisomy 13. Therefore, a direct karyotyping was immediately performed. Next, the patient was qualified for amiodarone transplacental therapy. Follow-up scans revealed a reduction in nuchal translucency thickness, no signs of fetal oedema, restoration of sinus rhythm, and a normal flow profile in the ductus venosus. At 18 weeks and 4 days the therapy was terminated. The baby was born at 39 weeks of gestation through natural labour. Neonatal mass was 3840 g, and 10 points were scored on the Apgar scale. No abnormalities were found in ECG and neonatal echocardiography. The definitive cause of late first trimester supraventricular tachycardia in the described case has not been determined.